Metaphorical conceptualizations of marketing - BURCEA, Raluca Gabriela (Annals of Spiru Haret University. Economic Series, 2010)
Currently, the centrality of marketing to enhancing the prosperity of businesses, individuals and even society is an undeniable fact. Marketing has emerged as a field worthy of being investigated by both marketing theorists and practitioners and specialized discourse researchers. Since the apprehension of the highly complex and abstract marketing notions cannot be achieved spontaneously, metaphor represents a valuable tool for providing a better understanding of the domain in question. In this context, our paper aims to explore three of the most relevant conceptual metaphors used in relation to marketing, namely the MARKETING IS MOVEMENT, the MARKETING IS MILITARY CONFLICT and the MARKETING IS A RELATIONSHIP conceptual metaphors. Relying on a corpus formed of two notable works on marketing, we highlight the main linguistic realizations of the above-mentioned metaphors, with a focus on their emergence and prominence in close connection with the shifts in the conceptual paradigm of marketing.